Online Shopping Behavior of Health Products During Pandemic Related to Public Education by Indonesian FDA - Elsadora Reapina Malthaputri; Yos Sunitiyoso (AIBPM Publisher, 2021)
The COVID-19 pandemic has changed many things in people's lives, including people's behavior in shopping. Previous findings that showed an increase in a transaction in the online market during the pandemic indicated a change in consumer behavior shifting to online shopping. One of them is in the product category of health products. This study seeks to see these effects and to find things that are of concern to the public when shopping for health products online by exploring several aspects: 1) Consumer's insight on online shopping for health products, 2) Perception on pandemic effect on shopping frequency, 3) Behavior of online shopping for health products, and 4) Perception on online shopping for health products experience. The methodology was quantitative, data collection was carried out by survey and descriptive data processing. Findings of this study show there has been an increase in online shopping for health products during the pandemic, especially for supplement/ vitamin products. The shopping behavior found to have been good indicates that Indonesian FDA public education to the community runs well, while on other hand still faces several concerns. Most agreed that the COVID-19 pandemic made online shopping more frequent than before.